Lyapunov 재설계 방법을 이용한 무인 수상정의 군집 제어 - 우상범(Sangbum Woo); 이재용(Jaeyong Lee) (Han-guk haeyang gonghak hoeji (Online), 2014)
In this paper, a practical controller for a group of USVs is proposed in order to avoid matrix inversion problems in computation. Using nonlinear mapping, a formation composed of nonholonomic agents can be stabilized even when the formation is stationary. Since there is no matrix inversion in computing the control law, the computation complexity can be resolved. A controller for stabilizing the formation errors in the presence of model uncertainty is considered using the Lyapunov redesign method. The asymptotic stability of the formation errors is shown. It is also shown that the proposed controller can be applied to guide a formation to a different shape without modification.